Sustainable gelatin-based packaging with nanoemulsified chilli seed oil for enhancing poultry meat preservation: An eco-friendly approach - Jahangir A Rather; Gurkirat Kaur; Irshad A Shah; Darakshan Majid; Hilal A Makroo; B.N. Dar (Food Chemistry Advances, 2024)
Utilizing poultry feet, a typically underutilized by-product, we extracted gelatin to fabricate environmentally friendly packaging pouches for the shelf life enhancement of fresh chicken breast cubes. The incorporation of chilli seed oil nanoemulsions, characterized by their particle sizes (61-127 nm) and zeta potential values (-18 to -28 mV), not only contributed to the pouches' structural integrity but also imparted antimicrobial properties. These pouches demonstrated reduced UV light transmittance and controlled color changes in packaged chicken breast cubes, compared to the control samples. Significantly, the pouch-packaged samples exhibited slower pH increase, reduced weight loss (16.2-20.4%), and lower TBARS values, indicative of delayed lipid oxidation and spoilage. Microbiological assessments revealed that the packaged samples effectively restrained microbial growth, staying within safety limits for E. coli and total plate counts, unlike the control samples which exceeded these thresholds. Textural analysis further showed better preservation of the meat's consistency within the pouches. This investigation not only highlights the valorization of food industry by-products in developing sustainable packaging solutions but also emphasizes the efficiency of developed packaging pouches in enhancing shelf-life of fresh poultry meat cubes, thus resonating with the contemporary needs of food processing technologies and consumer acceptance.